EFEKTIVITAS KONTAINER DENGAN ATRAKTAN PAKAN IKAN LELE (APIL) SEBAGAI PENGENDALIAN LARVA NYAMUK AEDES AEGYPTI DI PUSKESMAS KOTA BENGKULU - Jubaidi; Okfianti, Putri; Mulyati, Sri (Jurnal Sanitasi Profesional Indonesia, 2024)
A black container (bucket) filled with water and added with catfish feed attractant (PIL) emits an odor approximately two days later that can attract Aedes aegypti mosquitoes to lay eggs. The PIL-filled container can indirectly reduce the population of Aedes aegypti mosquitoes. This mosquito is a vector of dengue fever (DF), which is a public concern. The aim of the study is to reduce the population of Aedes aegypti mosquitoes using PIL at concentrations of 0.06, 0.09, 0.12, 0.16, and 0.20 grams. The type of research used is a quasi-experiment, with a posttest-only control design and six treatments. The materials and tools used in this study include containers, clean water, and the addition of PIL. The population consists of 20 community health centers in Bengkulu City, with a sample of 4 community health centers selected through purposive sampling as locations for placing 160 containers. The results showed that the data were not normally distributed (p<0.05), so the Kruskal-Wallis test was used for hypothesis testing. The total number of Aedes aegypti larvae found in the treatment and control containers was 3,735 larvae, with 160 containers serving as breeding sites. The Kruskal-Wallis test results showed a significance value of 0.002 < 0.05, meaning the hypothesis was accepted, indicating a difference in the average between the treatment containers and the control containers. This study was effective in reducing the Aedes aegypti mosquito population in Bengkulu City. Further research is needed with other mosquito trap models.